BioMagz with an Approach to Socio-Scientific Issues as a Learning Resource to Learn Environmental Change Materials to Improve Scientific Literacy - Aditya Kusuma Dewi; Yuyun Maryuningsih; Mujib Ubaidillah (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
Students’ limited learning resources result in low scientific literacy ability. Therefore, additional interesting learning resources are needed to improve the students’ scientific literacy skills. One of the appropriate learning resources is BioMagz with an approach to socio-scientific issues. This research focuses on the material of environmental changes. This study aims to: (1) develop BioMagz with an approach to socio-scientific issues to improve the scientific literacy of environmental changes and (2) apply BioMagz with an approach to socio-scientific issues to increase the scientific literacy of environmental change materials. This development research employed the ADDIE model (analysis, design, development, Implementation, and evaluation) and was conducted at SMAN 1 Kadipaten. The experts’ validation and students’ responses show that the BioMagz with an approach to socio-scientific issues has a score of more than 86%. It concludes that BioMagz with an approach to socio-scientific issues is very feasibly implemented in learning. The hypothesis test on the scientific literacy ability variable has obtained a significant value of less than 0.005. This score indicates that H0 is rejected and the use of BioMagz with an approach to socio-scientific issues in learning can increase students' scientific literacy skills.